Resilience of Arctic Communities: Socio-Economic Aspect - Nikulkina, Inga V.; Gordyachkova, Olga V.; Sukneva, Svetlana A.; Romanova, Elena V.; Gherardi, Jeanne; Wardekker, Arjan; Antonova, Marina E. (International Journal of Criminology and Sociology, 2021)
The study investigates factors that directly or indirectly affect the development of settlements in the North-East of the Russian Arctic. The study highlights the specific features of the Arctic settlements of the Northeast, as well as factors that will be considered in the development of a methodology for assessing the resilience of Arctic communities to economic shocks. The main focus is on the investigation of demographic processes in the Northeast Arctic, since it is human capital that determines the resilience of settlements to economic shocks. According to the results of the analysis, it was found that the key trend is the migration outflow, and the factors constraining it are the growth of wages, the presence of a minimum improvement of housing, in particular, heating and guarantees of social support. Therewith, such a factor as the presence of traditional trades and occupations does not contribute to a decrease in the migration outflow. This study was performed to further develop the concept of resilience and form a methodology for assessing the resilience of the economic and social system of an Arctic settlement to economic shocks. In the future, this methodology makes provision for the construction of a model with factors and indicators that determine the resilience of the socio-economic system of the Arctic settlement in the North-East of Russia (as exemplified by the Bulunsky district of the Republic of Sakha (Yakutia)) to economic shocks.